Association of prolonged QTc interval with Takotsubo cardiomyopathy: A neurocardiac syndrome inside the mystery of the insula of Reil. Issue 4 (17th April 2018) - Marafioti, Vincenzo; Turri, Giulia; Carbone, Vincenzo; Monaco, Salvatore
Abstract : The Takotsubo cardiomyopathy is often considered autochthonous to the heart, although the primary problem may be not in the heart muscle itself. Instead, similar to several Takotsubo‐like cardiac pathologies seen in acute neurological diseases, it may reflect the capacity of the nervous system to injure the heart. Persuasive evidence exists that shocking emotional stress promotes direct heart injuries. Moreover, clinical and laboratory research shows that cardiac structural damage can occur in the presence of a normal heart, especially in the context of seizures, stroke, and traumatic brain injury or under conditions of psychological stress. The aim of this review is to summarize the clinical implications of these observations, several of which focus on the pivotal role of the insula of Reil in the brain‐heart connection, to unravel the mystery of Takotsubo cardiomyopathy pathogenesis.